Sap flow and water potential in tomato plants (Solanum lycopersicum L.) under greenhouse conditions (2018)
The tomato is one of the most important horticultural fruits in the world, with large scale horticultural production in Colombia, as seen in the cultivated area of 8,992 and 345,291 t produced. The development of this crop requires production areas under controlled conditions (greenhouses) because it is important to monitor the water status of the plants to achieve successful development. In order to predict the behavior of the water potential of xylem (ᴪ) and sap flow (FH2O) in relation to environmental variables (RAFA, HRa, Ta, DPV), a mechanical model of water flow in tomato plants (Solanum lycopersicum L.) was used under greenhouse conditions in Colombian Amazon piedmont (Florencia, Caquetá). The daily-monitored trends remained between 64.7 and 225.4 g h-1 and -1.2 to -0.34 MPa for FH2O and ᴪ, respectively. To model the behavior of the variables, these trends were between -0.38 and -1.30 MPa for ᴪ and 58.46 and 208.55 g h-1 for FH2O, which were highly correlated (P<0,0001). The use of a mechanical model of water flow in tomato plants under greenhouse conditions proved to be statistically and physiologically feasible for understanding the daily water demand and so can be a source of information when designing irrigation plans.